Household Saving in China: The Keynesian Hypothesis, Life‐Cycle Hypothesis, and Precautionary Saving Theory. (December 2013) - Liu, Shenglong; Hu, Angang
<x xml:space="preserve">Abstract</x> We test the explanatory powers of Keynesian theory, the life‐cycle hypothesis, and the precautionary saving theory on household saving in China, based on data from 1990 to 2009 from 31 provinces and autonomous regions. The results show that the precautionary saving motivation explains household saving better than Keynesian theory. The study results also highlight the impact of life expectancy on China's household saving.